Transforming an Orthopaedic Unit Into an "Age-Friendly" Unit Through Implementation of the American Geriatrics Society's CoCare: Ortho Program. Issue 5 (May 2022) - Shen, Jenny Y.; Mendelson, Daniel Ari; Lang, Valerie J.
Abstract : Objective: To transform an inpatient orthopaedic unit into an age-friendly unit for geriatric fracture center (GFC) patients. Design: Pragmatic dissemination study of a continuous quality improvement intervention with episodic data review. Setting: Large quaternary care university hospital with no on-site geriatrics program and no dedicated geriatric inpatient unit. Participants: Individuals 60 years of age and older with fragility fracture of the native proximal femur hospitalized from July 2017 to June 2020. Intervention: A hospital medicine-orthopaedics comanagement model for a GFC was developed using processes, tools, and education provided by the American Geriatrics Society's AGS CoCare: Ortho program to support the age-friendly 4Ms principles: mentation, mobility, medications, and what matters. Delirium reduction strategies included minimizing sleep interruption through changes in blood draw times, order sets for pain management, and nursing education. Mobility specialists were incorporated to improve early mobilization on the orthopaedic unit. Main Outcome Measurements: Frequency of weight-bearing on postoperative day 1 and frequency of delirium among GFC patients on the orthopaedic unit were compared with those among concurrent GFC patients on other units. Results: Frequency of delirium was 26% among patients on the orthopaedic unit versus 35% among those on other units ( P = 0.055). Frequency of weight-bearing on post-operative day 1 was 84% among patients on the orthopaedic unit versus 72% among those on other units ( P = 0.003). Conclusions: AGS CoCare: Ortho is an effective dissemination program for establishing a hospital medicine-orthopaedics comanagement program and making an orthopaedic unit age-friendly in a hospital without onsite geriatricians or a dedicated geriatrics unit. Level of Evidence: Therapeutic Level III. See Instructions for Authors for a complete description of levels of evidence.